Analisis Trading Volume Activity dan Abnormal Return Sebelum dan Sesudah Stock Split pada Perusahaan yang Listing di BEI Tahun 2019-2022 - Hidayati Amelia Rahayu; Faizal Satria Desitama (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study was conducted with the aim of seeing the difference in trading volume activity (TVA) and abnormal stock returns before and after the stock split on issuers listed on the Indonesia Stock Exchange for the 2019-2022 period. This research uses a quantitative approach, with the type of research being an event study. The event study analysis period was carried out with an observation period of 5 days before the stock split, 1 day after the stock split, and 5 days after the stock split, so that the number of research periods was 11 days. The population in this study was 380, while the sample used was 34 issuers. The sampling method used is purposive sampling. This study used a secondary type of data source, where the entire data was obtained from the official website or website of the Indonesia Stock Exchange (IDX). The variables used are independent variables in the form of stock splits, as well as dependent variables in the form of TVA and abnormal returns. Meanwhile, the data collection techniques used in this study are literature studies and documentation studies. The test results for the TVA variable using the Wilcoxon signed-rank test showed that there was a difference in TVA before and after the stock split action by the issuer. Meanwhile, testing for abnormal return variables using paired sample t-tests, shows the results that there is a difference in abnormal stock returns both before and after the stock split action by issuers. Keywords: Trading Volume Activity, Abnormal Return, Stock Split